The cortical neuroimmune regulator TANK affects emotional processing and enhances alcohol drinking: a translational study - Müller, Christian P.; Chu, Congying; Qin, Liya; Liu, Chunyu; Xu, Bing; Gao, He; Ruggeri, Barbara; Hieber, Saskia; Schneider, Julia; Jia, Tianye; Tay, Nicole; Akira, Shizuo; et al. (Cerebral cortex, 2019)
Abstract: Alcohol abuse is a major public health problem worldwide. Understanding the molecular mechanisms that control regular drinking may help to reduce hazards of alcohol consumption. While immunological mechanisms have been related to alcohol drinking, most studies reported changes in immune function that are secondary to alcohol use.